Characterising professional drivers' exposure to traffic-related air pollution: Evidence for reduction strategies from in-vehicle personal exposure monitoring. (August 2021) - Lim, Shanon; Barratt, Benjamin; Holliday, Lois; Griffiths, Chris J.; Mudway, Ian S.
Highlights: Largest study to characterise personal BC exposure for professional drivers. Participants exposures were 2.6 times higher at work compared to not at work. Professional drivers experienced high peaks in exposure (>100 µg/m 3 ) while driving. Tunnels, location, day of week and time of shift were determinants of BC exposure. Driving with windows closed significantly reduced drivers' exposure. Abstract: Professional drivers working in congested urban areas are required to work near harmful traffic related pollutants for extended periods, representing a significant, but understudied occupational risk. This study collected personal black carbon (BC) exposures for 141 drivers across seven sectors in London. The aim of the study was to assess the magnitude and the primary determinants of their exposure, leading to the formulation of targeted exposure reduction strategies for the occupation. Each participant's personal BC exposures were continuously measured using real-time monitors for 96 h, incorporating four shifts per participant. ' At work ' BC exposures (3.1 ± 3.5 µg/m 3 ) were 2.6 times higher compared to when 'not at work' (1.2 ± 0.7 µg/m 3 ). Workers spent 19% of their time 'at work driving', however this activity contributed 36% of total BC exposure, highlighting the disproportionate effect driving had on their daily exposure. Taxi drivers experienced the highest BC exposures due to the time they spent working in congested central London, while emergency services had the lowest. Spikes in exposure were observed while driving and were at times greater than 100 µg/m 3 . The most significant determinants of drivers' exposures were driving in tunnels, congestion, location, day of week and time of shift. Driving with closed windows significantly reduced exposures and is a simple behaviour change drivers could implement. Our results highlight strategies by which employers and local policy makers can reduce professional drivers' exposure to traffic-related air pollution.